Ensino de geografia: pesquisas em tecnologias digitais de informação e comunicação no ensino fundamental (2019 - 2024) - Mendonça, Rodrigo Alves de (2024)
In the face of technological advancements in information and communication across various fieldsof knowledge, numerous challenges arise from this new reality. Ineducation, for instance, among the new obstacles to overcome, we encounter faulty and unequal infrastructure, the training of stakeholders, and the need for social inclusion. In a vision where schools play a transformative role in society, promoting citizenship and personal development with an emphasis on democratic management, this research focuses on the use of Digital Information and Communication Technologies (DICT) as teaching strategies for Geography in basic education, specifically in the final years of Elementary School. The objective is to identify and catalog theses and dissertations where innovative practices related to teaching mediation and learning enhancement through the use of DICTare detailed by researchers. The research centers around the question: “What digital technological strategies can be used in teaching Geography in the Final Years of Elementary School?” A survey will be conducted on dissertations and theses from the period 2019 to 2024 to create an educational resource catalog, subsequently made available on the blog https://estrategias-didaticas-digitais.blogspot.com/. The period was chosen to capture the reality caused by the Covid-19 epidemic in its different academic moments: pre-shutdown of basic education, distance learning, and the return to in-person activities. Given these realities, the role of cartography as a teaching toolfor Geography content remained predominant, as seen in the various studies reviewed.